CONTENT ANALYSIS OF RAYMOND CHIN YOUTUBE VIDEO "WHY YOUR INVESTMENTS MAKE YOU POOR – WARREN BUFFETT" - Dimas Hafizah Abimanyu; Hilman Fariz Alfaridzi; Muhamad Fauzi; Arif Nur Suryo Hadi; Lintar Huzein Rumasoreng; Sonya Trikandi; Febri Sari Siahaan (Journal of Social and Economics Research, 2026)
This study aims to analyze the key messages, moral values, and crucial quotes contained in Raymond Chin’s YouTube video titled “Why Your Investments Make You Poor – Warren Buffett”. Amidst the prevalence of instant-gratification culture and social media pressures that drive the younger generation to make impulsive investment decisions, the video serves as a counter-narrative highlighting Warren Buffett’s long-term investment philosophy. The study employs a qualitative approach with a descriptive design, utilizing qualitative content analysis and document study methods. Data collection was conducted in three stages: comprehensive observation of the video content, verbatim transcription, and the identification of quotes based on timestamps. The analysis reveals that Raymond Chin’s video consistently emphasizes three fundamental pillars of financial success: strategic patience, a focus on one’s "circle of competence," and emotional discipline. These findings underscore that the investment failures experienced by many individuals stem not from a lack of knowledge, but rather from a psychological inability to persevere through a long-term process fraught with uncertainty. The study concludes that sustainable financial success requires consistency, emotional control, and a deep understanding of the compounding effect, rather than speed in achieving results.